Developing Video-Based Quran Memorization Media Using the Talqin Method for Elementary School Students - Hartanto, Rudy; Khoir, Mulyanto Abdullah (Abjadia : International Journal of Education, 2025)
This study aims to develop video-based Quran memorisation learning media using the talqin method to improve elementary school students' memorisation. The background of this study is the need for learning media that is interesting, effective, and appropriate to the characteristics of early childhood in memorising the Quran. The research method used is Research and Development (RD) with the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The subjects were elementary school students participating in the Quran memorisation program. Expert validation results indicate that the developed media is categorised as very feasible, both in terms of material and media aspects. Limited trials showed a significant increase in students' memorisation abilities between the pretest and posttest. In addition, students' responses to the video media were very positive because they were considered easier, more enjoyable, and helped with the process of repetition. Thus, video-based learning media using the talqin method is effective in improving elementary school students' Quran memorisation.